Recovering Dense Stereo Depth Maps Using a Single Gaussian Blurred Structured Light Pattern - Xida Chen; Yee-Hong Yang (2013 International Conference on Computer and Robot Vision (CRV), 2013)
In this paper, we present a new single shot structured light method to recover dense depth maps. Contrary to most temporal coding methods which require projecting a series of patterns, our method needs one color pattern only. Unlike most single shot spatial coding methods which establish correspondence along the edges of the captured images, our method produces a dense set of correspondences. Our method is built based on a new important observation that a Gaussian blurred De Bruijn pattern preserves the desirable windowed uniqueness property. A Gaussian blurred De Bruijn pattern is used so that the color of every illuminated pixel is used to its fullest advantage. The simulated experiments show that the proposed method establishes a correspondence set whose density and accuracy are close to that of using a temporal coding method. We also demonstrate the robustness of our approach by applying it to several real-world datasets.